HIV Infection: Immunopathogenesis and Risk Factor to Fishermen - Retno Budiarti (Universitas Hang Tuah, 2018)
AIDS (Acquired Immuno Deficiency Syndrome) caused by HIV (Human Immunodeficiency Virus) infection, is still one of the infectious diseases that causes fatalistic and have not already found a universal and reliable vaccine. As the name given to the virus as well as the disease it causes, the signs and symptoms experienced by the sufferer are persistent and severe disorders of the body's defense mechanism against the disease, or the person's immunological system.Epidemiology of AIDS in Indonesia, which is a tropical country and its territory is mostly sea area still high, even East Java was the highest accumulatively until March 2016. HIV infection itself until March 2016, East Java accumulatively was on the second level after DKI Jakarta. Based on the data of The Ministry of Health during 2014, farmer and fishermen were on the fourth level of AIDS in Indonesia.This mechanism of immune system disorders by HIV is important to explain and understand, so that current researchs, as well as in the future, can solve the problems posed by this viral infection, either by the discovery of vaccines or their preventive measures, formulation of a therapeutic management which is reliable.